Business process benchmarking : finding and implementing best practices - Camp, Robert C., 1935- (Milwaukee, Wis. : ASQC Quality Press, 1995)
Building upon material from his previous runaway best-seller, Benchmarking: The Search for Industry Best Practices That Lead to Superior Performance, Camp provides a new focus on the leadership and management aspects of benchmarking. This new companion text includes several new case histories, and revisits the first four steps of Xerox Corporation's acclaimed ten-step benchmarking process.
Appendix E: Process Classification Scheme -- Appendix F: Process Inspection Checklist -- Appendix G: Roles and Responsibilities.
Includes bibliographical references (p. 407-422) and index.
Keywords: Benchmarking (Management)